Konsep Wahdatul Wujud dalam Pandangan Syekh Syamsuddin As-Sumatrani - Budi Handoyo (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Syamsuddin Asy-Syumatrani, the leading Sufi Ulama Sheikh who has influenced and developed Islamic intellectuality and spirituality in Aceh in the 16-17th century AD Wahdatul Wujud according to Syamsuddin Asy-Syumatrani is a teaching in philosophical Sufism, which explains that there is only one absolute form, namely Allah, while nature and humans are tajalli or madhar of Allah's nature. To understand this, he coined the concept of Wahdatul Wujud which is called the Dignity of Seven. Wahdatul Wujud is a concept to achieve our closeness to Allah SWT. But according to Syamsuddin asSumatrani Wahdatul Wujud is the Dignity of the Seven which consists of Ahadiyah, Wahdah, Wahidiyah, Spirit Realms, Mitsal Realms, Ajsam Nature and Human Nature. If we can understand the Seven Dignity, then we are united with God, which is what is called Wahdatul Wujud according to Syamsuddin asSumatrani. In fact, this Wahdatul Wujud can only be understood by feeling and revealing the unseen. However, most of the scholars until now have questioned the existence of wahdatul